Relationship between parenting styles and glycemic control in children with type 1 diabetes: a cross-sectional study in Iran - Ameneh rezaei; Daniel Zamanfar; Adele Bahar; Zahra Kashi; Reza Ali Mohammadpour; Forouzan Elyasi (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery)
Abstract Background and aim The Type 1 diabetes (T1D) management is a major challenge for families. Parenting styles are considered critical psychosocial factors influencing diabetes management outcomes. The present study investigated the relationship between parenting styles and glycemic control in children with T1D. Materials and methods This study is a cross-sectional study. The samples accordingly consisted of 110 parent–child pairs refereed to an endocrinology clinic in Iran in 2020. Demographic and Clinical Data and Parenting Styles and Dimensions Questionnaire-Short Form (PSDQ-SF) collected data. As a final point, the data were analyzed using the SPSS Statistics software and the associated tests. Results The Mean ± SD age of the children was 10.31 ± 2.23. Out of 110 parents, 108 cases were practicing the authoritative parenting style and two individuals had thus far adopted the permissive one. More authoritativeness practiced by parents was associated with improved glycemic control. A significant direct relationship was found between the sub-factor 2 of the authoritative parenting style and HbA1c and postprandial blood sugar (β = 0.342, p = 0.004 and β = 0.301, p = 0.02, respectively). Conclusions This study contributed to more understanding of the significant role of parental responsiveness in promoting good glycemic control.